Self-Love Starts from the Body: The Effect of Body Image Satisfaction on Student Self-Acceptance - Nur Fitriyah, Laily; Laily, Nadhirotul (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
College students are in a developmental stage that is vulnerable to social pressures, including demands related to physical appearance, which may affect body image satisfaction and levels of self-acceptance. Body image satisfaction was one of the important aspects in shaping self-acceptance, which ultimately contributed to students' psychological well-being. This study aimed to examine the relationship between body image satisfaction and self-acceptance among university students. The method used was quantitative correlational with regression analysis using four model approaches: linear, quadratic, logarithmic, and exponential. The participants consisted of 75 students selected through Accidental sampling. The results showed a significant relationship between body image satisfaction and self-acceptance, with the quadratic regression model being the best model to explain this relationship. The findings indicated that increased body image satisfaction could lead to higher self-acceptance up to a certain point, after which the effect leveled off. These results provided an understanding that although body image satisfaction played an important role in shaping self-acceptance, other factors also needed to be considered. The implication of this research encouraged higher education institutions to develop psychological interventions that supported the development of positive body image in order to enhance students' self-acceptance and overall mental health. Mahasiswa berada dalam fase perkembangan yang rentan terhadap tekanan sosial, termasuk tuntutan terhadap penampilan fisik, yang dapat memengaruhi kepuasan citra tubuh dan tingkat penerimaan diri. Kepuasan citra tubuh menjadi salah satu aspek penting dalam membentuk penerimaan diri, yang pada akhirnya turut menentukan kesejahteraan psikologis mahasiswa. Penelitian ini bertujuan untuk mengetahui hubungan antara kepuasan citra tubuh dan penerimaan diri pada mahasiswa. Metode yang digunakan adalah kuantitatif korelasional dengan analisis regresi menggunakan empat model pendekatan yaitu linear, kuadratik, logaritmik, dan eksponensial. Partisipan penelitian berjumlah 75 mahasiswa yang dipilih melalui Accidental sampling. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara kepuasan citra tubuh dan penerimaan diri, dengan model regresi kuadratik menjadi model terbaik dalam menjelaskan hubungan tersebut. Temuan ini menunjukkan bahwa peningkatan kepuasan citra tubuh dapat mendorong peningkatan penerimaan diri hingga titik tertentu, sebelum akhirnya efeknya melandai. Hasil ini memberikan pemahaman bahwa meskipun kepuasan citra tubuh penting dalam membentuk penerimaan diri, terdapat faktor lain yang juga perlu diperhatikan. Implikasi dari penelitian ini mendorong institusi pendidikan tinggi untuk mengembangkan intervensi psikologis yang mendukung pembentukan citra tubuh positif guna meningkatkan penerimaan diri dan kesehatan mental mahasiswa secara menyeluruh.